Duodenal expression of iron transport molecules in patients with hereditary hemochromatosis or iron deficiency - Dostalikova-Cimburova, Marketa; Kratka, Karolina; Balusikova, Kamila; Chmelikova, Jitka; Hejda, Vaclav; Hnanicek, Jan; Neubauerova, Jitka; Vranova, Jana; Kovar, Jan; Horak, Jiri (Journal of cellular and molecular medicine, 2012)
Disturbances of iron metabolism are observed in chronic liver diseases. In the present study, we examined gene expression of duodenal iron transport molecules and hepcidin in patients with hereditary hemochromatosis (HHC) (treated and untreated), involving various genotypes (genotypes which represent risk for HHC were examined), and in patients with iron deficiency anaemia (IDA). Gene expressions of DMT1, ferroportin, Dcytb, hephaestin, HFE and TFR1 were measured in duodenal biopsies using real-time PCR and Western blot. Serum hepcidin levels were measured using ELISA. DMT1, ferroportin and TFR1 mRNA levels were significantly increased in post-phlebotomized hemochromatics relative to controls. mRNAs of all tested molecules were significantly increased in patients with IDA compared to controls. The protein expression of ferroportin was increased in both groups of patients but not significantly. Spearman rank correlations showed that DMT1 versus ferroportin, Dcytb versus hephaestin and DMT1 versus TFR1 mRNAs were positively correlated regardless of the underlying cause, similarly to protein levels of ferroportin versus Dcytb and ferroportin versus hephaestin. Serum ferritin was negatively correlated with DMT1 mRNA in investigated groups of patients, except for HHC group. A decrease of serum hepcidin was observed in IDA patients, but this was not statistically significant. Our data showed that although untreated HHC patients do not have increased mRNA levels of iron transport molecules when compared to normal subjects, the expression is relatively increased in relation to body iron stores. On the other hand, post-phlebotomized HHC patients had increased DMT1 and ferroportin mRNA levels possibly due to stimulated erythropoiesis after phlebotomy.
Keywords: kationické antimikrobiální peptidy; železo; proteiny přenášející kationty; Humans; Case-Control Studies; Iron; messenger RNA; Cation Transport Proteins; lidé středního věku; Hemochromatosis; regulace genové exprese; studie případů a kontrol; Duodenum; Female; Aged; dospělí; hepcidiny; Phenotype; senioři; lidé; Hepcidins; Antimicrobial Cationic Peptides; Adult; RNA, Messenger; biologický transport; duodenum; ženské pohlaví; Gene Expression Regulation; Male; Middle Aged; fenotyp; hemochromatóza; Aged, 80 and over; senioři nad 80 let; deficit železa; mužské pohlaví; Iron Deficiencies; Biological Transport